Socio-Economic Problems of Today's High School Students in the Context of Reforming the Educational System of the Russian Federation - KRYUKOVA, Elena; STAROSTENKOV, Nikolai; KRAPOTKINA, Svetlana; TIMOSHINA, Elena; MAKEEVA, Dina; Yudina, Tatyana (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
The article considers the general issues of the current state and prospects of Russian higher education, problems of today's students studying at Russian universities and their possible solutions. The introduction of new generation educational standards is a necessary condition for international recognition of the Russian higher education, the possibility to integrate higher education and business, as well as for the solution of social and economic problems of high school students that can arise in the learning process. Vocational training will be developed at classical and modern universities. Supposed changes do not deny the existing forms of higher education.